2022
DOI: 10.1177/0734371x221078784
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing in the Public Sector: A Systematic Literature Review

Abstract: Public administration scholars have provided a variety of theoretical insights to understand bureaucratic whistleblowing, and have emphasized its ethical, legal, and practical rationales in the context of democratic bureaucracy. To enhance our understanding of this principled dissent behavior in the public sector, this study systematically reviews 71 whistleblowing articles and dissertations that address three aspects in the literature: (1) definitions and theories; (2) methods and data, and (3) factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 104 publications
1
8
0
Order By: Relevance
“…Thus, the fear of victims would appear to be a legitimate concern. This is consistent with the literature that shows people may fear blowing the whistle for fear of harm and reprisal (Kang, 2022). In addition, non-intervening bystanders reported feeling “guilt”, “sad” and “helpless”.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the fear of victims would appear to be a legitimate concern. This is consistent with the literature that shows people may fear blowing the whistle for fear of harm and reprisal (Kang, 2022). In addition, non-intervening bystanders reported feeling “guilt”, “sad” and “helpless”.…”
Section: Discussionsupporting
confidence: 93%
“…Whistleblowing is a deliberate non-obligatory act of disclosure of wrongdoings in an organisation by members to a person or organisation that may be able to act (Near and Miceli, 1995). Kang (2022) notes that whistleblowing consists of a process involving four elements: the whistleblower; the act or complaint; the receiver and the wrongdoer. It is for this reason that research has found that the likelihood of a person whistleblowing is influenced by multiple factors such as the psychological features of the whistleblower, the nature of the wrong-doing and the channels through which whistleblowing can occur (King, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between affective commitment and whistle-blowing is supported by prosocial behavior theory ( Dozier and Miceli, 2011 ; Nawawi and Salin, 2015 ). This theory states that an organization member has a sense of attachment to maintain and improve welfare ( Ahmad et al., 2014 ; Kang, 2022 ). Moreover, the action of whistle-blowing is an example of prosocial behavior based on the desire to guard the organization from misconduct.…”
Section: Discussionmentioning
confidence: 99%
“…Kang conducted a systematic review of whistleblowing in the public sector to examine methods and theoretical models [ 25 ]. The review included 71 peer-reviewed publications and dissertations in public administration, political science, and business.…”
Section: Introductionmentioning
confidence: 99%
“…Most empirical studies applied human resources, ethics, and psychology theories to assess individual, organisational, and situational factors associated with whistleblowing. Kang concluded that more research is needed on the frequency of whistleblowing, impact of leadership and training, effectiveness of legal protection systems, and consequences of whistleblowing [ 25 ].…”
Section: Introductionmentioning
confidence: 99%